Persepsi umat islam di negeri Kedah terhadap kaedah pembayaran zakat melalui perbankan internet - Ridzuan, Ahmad (2013)
Zakat payment through internet banking has been implemented by the Jabatan Zakat Negeri Kedah (JZNK) since 2005. This method turns out to save time, cost and effort of zakat payers. Payment of zakat can be executed anywhere, at anytime. However, traditional practices entrenched in the community where the payment of zakat performed in person with the 'akad', this internet banking methods sometimes cast doubt on society. In addition, there is also a debate about security issues and the negative perception of this transaction. Even after ten years of this method is introduced, the same issue still raised in the society. The objective of the study is to examine the public perception of the issues raised, their understanding and acceptance issues, analyze, and make recommendations as well as clarification on the issue. Quantitative methods in the questionnaire are used for the respondents and the results show that the acceptance and understanding of the method is still at a low level. Therefore, efforts should be enhanced by the relevant authorities, especially zakat institutions and banking institutions to encourage more people to use this facility